PENERAPAN MODEL PEMBELAJARAN CONCEPT ATTAINMENT DENGAN PENDEKATAN SAINTIFIK TERHADAP KEAKTIFAN BELAJAR SISWA PADA MAPEL EKONOMI - Sitanggang, Widya Indriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problems in this research is the implementation of attainment concept learning with scientific approach towards student learning activity in economics subject at Madrasah Aliyah Negeri 1 Pontianak.The form of this research was a quasy experiment design with nonequivalent control group design. About 38 students on experiment class, XI IPS 1 that is the lowest student learning activity given treatment use the attainment concept learning with scientific approach. In this research, data is collected by observation sheets of student learning activity, observation sheets of learning, interview teachers and students, and documentation learning. Analysis techniques the data used the descriptive analysis. The result showed that in general the application of attainment concept learning with scientific approach is going well, and increased of student learning activity from meeting 1 namely 58,64 % category sufficient and 67,90 % at a meeting 2 category good. It means attainment concept learning with scientific approach increased student learning activity on grade XI IPS 1 Madrasah Aliyah Negeri 1 Pontianak.Keywords: Attainment Concept Learning, Scientific Approach, Student Learning Activity